Experimental Study On The Development Of Tolerance And Withdrawal Syndrome To Pentylenetetrazole-Induced Seizures In Rats Treated With Retigabine - Elisaveta Apostolova; Vesela Kokova; Lyudmil Peychev (Journal of Biomedical & Clinical Research)
The aim of the study was to evaluate seizure liability in rats against the convulsant pentylenetetrazole (PTZ) during a 14-day treatment with retigabine (RTG). The seizure liability was also studied on the 1st, 2nd and 3rd day after the abrupt determination of its administration. Male Wistar rats were divided in groups of 10 and treated orally for 14 days (1st – 6th group with distilled water, and 7th – 12th group with retigabine (RTG) at a dose of 60 mg/kg bw The tolerance to the anticonvulsant effect of RTG was studied using subcutaneous injection of PTZ (120 mg/kg bw) on the 1th and 14th day. To determine the possible neuronal hyperexcitability on the 1st, 2nd and 3rd day after termination of drug administration, a lower dose of PTZ (65 mg/kg bw) was used. According to our results there was no change in the anticonvulsant activity of RTG during the whole period of treatment. The study on withdrawal syndrome showed slightly decrease of the effect on the first day after the last treatment, but with no significant difference to the controls. The anticonvulsant effect of RTG on the 2nd and 3rd day was close to that in the control group. Our results showed no development of tolerance on subchronic treatment with RTG. There was no significant change in the neuronal hyperexcitability on the 1st, 2nd and 3rd day after the termination of treatment. Based on these results we can suggest that RTG has no potential to develop withdrawal syndrome.